SOME ASPECTS ON THE REPRODUCTIVE BIOLOGY OF AN ENDEMIC CATFISH, ARIUS MANILLENSIS VALENCIENNES, 1840 (SILURIFORMES: ARIIDAE), OF LAGUNA DE BAY, PHILIPPINES - Ramos, Gliceria Ballesteros; Alfonso, Noel F (Malaysian Journal of Science, 2019)
Arius manillensis is an endemic and economically important catfish of Laguna de Bay, Philippines. This study generated data on some aspects of its reproductive biology that are vital for the enhancement of propagation efforts for inland fisheries in the Southeast Asian region. Monthly assessments were conducted for one whole year to establish the distinct spawning season(s) through determinations of gonadosomatic index (GSI), fecundity through counting the number of two classes of follicles, and size at sexual maturity. Sex ratio was taken into account. Peaks in GSI occurred in March to April and July to August. These peaks correspond with months of peaks in fecundity. The parallel patterns of these reproductive aspects strengthen the occurrence of two distinct spawning seasons. GSI did not show significant correlation with body parameters while fecundity was significantly correlated with body weight (BW) and length (BL) and gonad weight (GW). Size and weight of apparent sexual maturity or peak reproductive capacity is about 20 cm and 200 g, respectively. Sex ratio was female-biased (2.11: 1). Female dominance indicates a unique reproductive behavior of A. manilensis where males could have evolved survival mechanism(s) to elude capture during breeding seasons and evidently during spawning on the cold months.